Assessment of paracetamol toxic effects under varying seawater pH conditions on the marine polychaete hediste diversicolor using biochemical endpoints - Daniel, David (2022)
Increasing atmospheric carbon dioxide (CO2) levels are likely to lower ocean pH values, after its dissolution in seawater. Additionally, pharmaceuticals drugs are environmental stressors due to their intrinsic properties and worldwide occurrence. It is thus of the utmost importance to assess the combined effects of pH decreases and pharmaceutical contamination, considering that their absorption (and effects) are likely to be strongly affected by changes in oceanic pH. To attain this goal, individuals of the marine polychaete Hediste diversicolor were exposed to distinct pH levels (8.2, 7.9, and 7.6) and environmentally relevant concentrations of the acidic drug paracetamol (PAR: 0, 30, 60, and 120 µg/L). Biomarkers such as catalase (CAT), glutathione S-transferases (GSTs), acetylcholinesterase (AChE), and cyclooxygenase (COX) activities, as well as peroxidative damage (through thiobarbituric acid reactive substance (TBARS) quantification), were quantified to serve as ecotoxicological endpoints. Data showed a general increase in CAT and a decrease in GST activities (with significant fluctuations according to the tested conditions of PAR and pH). These changes are likely to be associated with alterations of the redox cycle driven by PAR exposure. In addition, pH levels seemed to condition the toxicity caused by PAR, suggesting that the toxic effects of this drug were in some cases enhanced by more acidic conditions. An inhibition of AChE was observed in animals exposed to the highest concentration of PAR, regardless of the pH value. Moreover, no lipid peroxidation was observed in most individuals, although a significant increase in TBARS levels was observed for polychaetes exposed to the lowest pH. Finally, no alterations of COX activities were recorded on polychaetes exposed to PAR, regardless of the pH level. The obtained results suggest that seawater acidification is detrimental to marine wildlife, since it may enhance toxic effects caused by environmental realistic concentrations of acidic drugs, such as PAR. This work was crucial to evidence that ocean acidification, in the context of a global change scenario of increased levels of both atmospheric and oceanic CO2, is a key factor in understanding the putative enhanced toxicity of most pharmaceutical drugs that are of an acidic nature.